2019
DOI: 10.1021/acsami.9b16862
|View full text |Cite
|
Sign up to set email alerts
|

Copper–Indium Binary Catalyst on a Gas Diffusion Electrode for High-Performance CO2 Electrochemical Reduction with Record CO Production Efficiency

Abstract: Copper-indium binary catalyst on a gas diffusion electrode for high-performance CO2 electrochemical reduction with record CO production efficiency. ACS Applied Materials and Interfaces 12 (1) , pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…7.0 in both treatments. The near neutral catholyte pH in BES 2 (−1.0 V/NaHCO 3 ) throughout the experiment may have prevented strong enrichment of acetogenic bacteria and consequently led to lower production of acetate and longer chain organic compounds.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…7.0 in both treatments. The near neutral catholyte pH in BES 2 (−1.0 V/NaHCO 3 ) throughout the experiment may have prevented strong enrichment of acetogenic bacteria and consequently led to lower production of acetate and longer chain organic compounds.…”
mentioning
confidence: 92%
“…A range of approaches, including electrochemical methods, have been developed to reduce CO 2 to valuable chemicals 3 . Over the past few decades, metal catalysts such as copper have been commonly used for electrochemical reduction of CO 2 and have received lots of attention in this area 4 7 . Microbial electrosynthesis (MES) is a bio-electrochemical technique that has offered the sustainable conversion of CO 2 to valuable organic chemicals at the cathode of bio-electrochemical systems (BES), using microorganisms as biocatalysts 8 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a further advantage is that the continuous flow reactor overcomes the low solubility of CO2 by using gaseous electrochemical reduction [14]. Thus, several papers have reported a current density of over 200 mA cm −2 when using the GDE [34][35][36]. Hence, the present section is focused on the device configuration and discusses the microfluidic cell, zero-gap electrolyzer, and multilayer electrolyzer stack that make commercialization possible.…”
Section: The Devicementioning
confidence: 99%
“…Five CSs, all based on ERCO 2 to FA/formate using Sn-based electrodes in aqueous electrolyte, reported in the literature and characterised by particularly good performances and by usage of relatively cheap materials and simple cell designs were selected. [15,17,18,20,30] Indeed, most of the investigated technologies in the literature were based on the usage of more expensive cathodes (including core-shell structured Cu 2 O/Cu@C immobilized on nitrogen-doped graphene sheets (Cu2O/Cu@C/ NG), [31] Bi 2 O 2 CO 3 nanosheets, [32] Sn(S)/Au nanoparticles, [33] BiÀ SnO/Cu foam, [34] SnCu alloys, [35] Ag x Sn y alloys, [36][37] In x Sn y alloys, [38,39] Sn x Pb y alloys, [40] Sn x Pb y Bi z alloys, [41] Cu x In y alloys, [42][43][44][45] Pd-, [46] PdPt- [47] or Bi-based catalyst, [48][49][50] etc.) or more complex reactor designs, which are more difficult to scale-up.…”
Section: Description Of the Case Studiesmentioning
confidence: 99%
“…Furthermore, it was demonstrated that operating pressures up to 20 bar could be economically viable. [42] Also, Ramdin et al [30] have performed the ERCO 2 using a Sn plate cathode and HP system; however, they used a divided semi-continuous batch cell equipped with bipolar membranes (BPMs) driving the reaction at 30 mA cm À 2 with a FE of approximately 80 % (CS V). The remarkably discover of these researchers was a cheaper BMP that can maintain a different compartment pH between anodic and cathodic compartment at high P CO2 .…”
Section: Description Of the Case Studiesmentioning
confidence: 99%